A Case Study of Reverse Engineering Integrated in an Automated Design Process - Pescaru, Roxana; Kyratsis, Panagiotis; Oancea, Gheorghe (IOP Publishing, 2016)
This paper presents a design methodology which automates the generation of curves extracted from the point clouds that have been obtained by digitizing the physical objects. The methodology is described on a product belonging to the industry of consumables, respectively a footwear type product that has a complex shape with many curves. The final result is the automated generation of wrapping curves, surfaces and solids according to the characteristics of the customer's foot, and to the preferences for the chosen model, which leads to the development of customized products.